2004
DOI: 10.1038/oby.2004.114
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Migration in Adipose Tissue of Mice Null for ICAM‐1 and Mac‐1 Adhesion Receptors

Abstract: Results: ICAM-1 was expressed in adipose tissue and localized to the vascular endothelium. Macrophages and lymphocytes were prevalent within the stromal-vascular cell fraction of adipose tissue, and gender-specific differences were observed, with adipose tissue from female mice containing significantly more macrophages than tissue from male mice. Numbers of leukocytes in ICAM-1 Ϫ/Ϫ and Mac-1 Ϫ/Ϫ mice were not different from wild-types, however, indicating that these adhesion receptors are not required for leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 22 publications
(19 reference statements)
7
51
0
1
Order By: Relevance
“…4A). Region 1 contained lymphocytes consistent with the previously published results (7,32). ICAM-1 expression in this region was low, compared with cells in regions 2 and 3 (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4A). Region 1 contained lymphocytes consistent with the previously published results (7,32). ICAM-1 expression in this region was low, compared with cells in regions 2 and 3 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…This is the first demonstration of relatively rapid changes in a specific population of macrophages in adipose tissue, corroborating longer term studies that have correlated increases in adiposity with increased F4/80ϩ macrophage infiltration into adipose tissue (32,50,53). Only the F4/80ϩ populations expressing CD11c and CD14 increase in response to a high-fat diet.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous reports showed that the expression of adhesion molecules in adipose tissue was increased in the obese condition [5,6] and a different study indicated that HFD induced obese mice exhibited higher expression of Intercellular adhesion molecule 1(ICAM-1) and Vascular cell adhesion [7]. Thus, adhesion molecules affect obesity-induced macrophage infiltration into adipose tissue.…”
Section: Introduction *mentioning
confidence: 97%
“…Furthermore, the number of leukocytes in the adipose tissue of ICAM-1-deficient mice and Mac-1-deficient mice fed HFD were the same as in the WT mice fed HFD. Consequently, these adhesion receptors are not required for leukocyte migration into adipose tissue (34).…”
Section: Discussionmentioning
confidence: 99%